Potencial risk in the highway infrastructure - García Depestre, René Antonino (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2020)
In Cuba the analysis of the risks in the infrastructure of highways is carried out by means of individual analysis of the elements of the safety road. In the work the risks are analyzed using like base international Marco for the adaptation of the infrastructure of highways in the face of the climatic change, developed by the World Association of the Highway in the 2015, incorporating the state of the elements of the highway and the parameters of exploitation, determining the potential risks. Starting from the results a proposal of measures is made for the mitigation of the identified problems.